ANALISIS ISI ETNOGRAFIS: GAYA JURNALISME MEDIA BARU PADA BERITA DI PLATFORM TIKTOK - Wike Widyaswarawati; Nurul Hasfi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Technology of communication is growing from time to time. Nowadays, online media is very helpful for people to get information quickly and widely. Likewise, newspaper companies are currently using social.media as a means of delivering news. One of the social media is Tiktok aplication. It provides some features for making short creative videos and publishing them to public. The visuals of the news published on Tiktok are free and various so that they can attract the number of viewers. Although, the information or news which is delivered must be accurate and prioritize quality of jurnalism and applyi ethich codes of jurnalism well. Therefore, in this study, the author wants to explore how journalism quality on news videos from the official news account on Tiktok is. This research is a qualitative research method with an ethnographic content analysis type. While the data collection technique in this study is in the form of news documentation. There are 30 news videos on 3 official news accounts on Tiktok, namely @kompascom, @liputan6com, and @patroli_indosiar. The results of the study show that the use of journalism style in news videos on Tiktok is applied on the video sampling. Most of these news videos use an inverted pyramid, but their titles are still clickbait. They are not in accordance with EYD rules, the writing of the news terrace do not fulfills indicators of 5W + 1H, and the news writing does not meet the indicators of journalism ethics rules.